Rolling and adhesion of human tumor cells on vascular endothelium under physiological flow conditions. - Giavazzi, R; Foppolo, M; Dossi, R; Remuzzi, A (The Journal of Clinical Investigation, 1993)
We investigated the interaction of different human tumor types with resting and IL-1-activated human umbilical vein endothelial cells under laminar flow conditions using a parallel plate flow chamber. Three tumor cell lines (the HT-29M colon carcinoma, the OVCAR-3 ovarian carcinoma, and the T-47D breast carcinoma) showed limited adhesion to unstimulated endothelial cells at any of the shear stress levels tested, while rolling and massive adhesion of tumor cells were observed on IL-1-activated endothelial cells. Three other tumor cell lines (the A375M and A2058 melanomas and the MG-63 osteosarcoma) did not adhere on resting endothelial cells at high shear stress (> 1.5 dyn/cm2) and started to adhere with decreasing shear stress; the number of adherent cells increased steeply on IL-1-activated endothelial cells, but no cell rolling was observed even at the highest shear stress. These mechanisms of tumor cell interaction with endothelial cells were analyzed in detail using the HT-29M colon carcinoma and the A375M melanoma. Incubation of activated endothelial cells with a monoclonal antibody against E-selectin inhibited rolling and adhesion of HT-29M, but had no effect on the adhesion of A375M cells; monoclonal antibody against vascular cell adhesion molecule-1 reduced the adhesion of A375M cells and had no effect on HT-29M. The selective interaction of these two molecules with tumor cells was confirmed by measuring the adhesion of tumor cells on immobilized soluble proteins. On E-selectin-coated surfaces, HT-29M cells rolled during perfusion experiments without subsequent adhesion, while A375M cells did not adhere. On vascular cell adhesion molecule-1-coated surfaces, HT-29M cells neither adhered nor rolled, while A375M cells adhered massively without rolling. Under flow conditions, therefore, cells from different tumor types interact with the endothelial surface by different mechanisms, depending on adhesion molecules expressed on the tumor and endothelial cell surface. Images